STRATEGI KOMUNIKASI KORPORASI DAN DAMPAKNYA TERHADAP BRAND IMAGE: STUDI KASUS STARTUP TRANSPORTASI MAXIM DI INDONESIA - Diane Derlin; Selena Dennysal (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
This study aims to analyze the corporate communication strategies implemented by thetransportation startup Maxim in Indonesia and evaluate their impact on brand image from theconsumer perspective. In the increasingly competitive online transportation industry,corporate communication plays a strategic role in shaping public perception and strengtheningbrand positioning. This research employs a quantitative approach using a survey method,distributing questionnaires to 150 respondents who are active Maxim users in urban areas.The collected data were analyzed using IBM SPSS version 26 with multiple linear regressionto examine the relationship between corporate communication strategy variables (digitalcommunication, external communication, crisis communication) and brand image. The resultsindicate that corporate communication strategies have a positive and significant effect onMaxim’s brand image. Digital and external communications are the most dominant factorsinfluencing consumer brand perception. These findings provide significant implications forstartups in developing adaptive, consistent, and audience-relevant communication strategiesto enhance brand value in a competitive market.Keywords: corporate communication strategy, brand image, startup, Maxim, digitalcommunication.